Crisis prevention as a chance for business recovery in the European Union - Đurić Đuro M.; Jovanović Vladimir M.; Jovanović Marija S. (Ekonomija: teorija i praksa)
With the entry into force of Directive No. 2019/1023 on Frameworks for Preventive Restructuring, clear and transparent legal instruments were introduced for crisis prevention in business operations of economic entities throughout the single market of the European Union. They involve early detection of circumstances that may lead to insolvency and encourage a response without delay. The key goal is to overcome the debtor's financial difficulties at an early stage, and when possible, prevent insolvency and ensure business sustainability. With the introduction of new instruments into the national legislation, the area traditionally governed by the norms of bankruptcy law, which are mostly of an imperative nature, has been entered. This was done by defining the circumstances that precede the reasons for bankruptcy and by providing instruments to protect the debtor from enforcement. The new instruments, on the other hand, are of a consensual legal nature, that is, governed by dispositive norms. The authors of this paper analyze the preventive instruments, their way of introduction into the legislation, as well as the particularity of the new legal regime in important economies in the EU, using the normative and comparative law method. This article presents an analysis of the application of the new regulations, which have been in force for two years, and the results of their implementation.